Victoria Woodhull's Sexual Revolution : Political Theater and the Popular Press in Nineteenth-Century America - Frisken, Amanda (Book collections on Project MUSE., 2004)
"Victoria Woodhull, the first woman to run for president, forced her fellow Americans to come to terms with the full meaning of equality after the Civil War. A sometime collaborator with Susan B. Anthony and Elizabeth Cady Stanton, yet never fully accepted into mainstream suffragist circles, Woodhull was a flamboyant social reformer who promoted freedom, especially freedom from societal constraints over intimate relationships. This much we know from the several popular biographies of the nineteenth-century activist. But what we do not know, as Amanda Frisken reveals, is how Woodhull manipulated the emerging popular media and fluid political culture of the Reconstruction period in order to accomplish her political goals." "Using contemporary sources such as images from the "sporting news," Frisken takes a fresh look at the heyday of this controversial women's rights activist, discovering Woodhull's previously unrecognized importance in the turbulent climate of Radical Reconstruction and making her a useful lens through which to view the shifting sexual mores of the nineteenth century."--Jacket